Four Months of a School-Based Exercise Program Improved Aerobic Fitness and Clinical Outcomes in a Low-SES Population of Normal Weight and Overweight/Obese Children With Asthma - Lu, Kim D.; Cooper, Dan M.; Haddad, Fadia; Radom-Aizik, Shlomit (Frontiers in Pediatrics, 2018)
Introduction: Fitness can improve asthma management. However, children from disadvantaged and minority communities generally engage less in physical activity, and have increased obesity and asthma disease burden. The goal of this pilot study is to evaluate 1) the feasibility of an exercise intervention program in a school-based setting and 2) the effect of the intervention on fitness, asthma, and clinical outcomes in normal weight and overweight/obese children with asthma from low-SES population. Materials and methods: Nineteen children, ages 6–13 years, from two elementary schools in Santa Ana, CA, a population with high percentage of Hispanic and low socioeconomic status, participated in the study. Training sessions occurred at the schools during afterschool hours (3 sessions per week x 4 months). Before and after the intervention, evaluations included pulmonary function testing, cardiopulmonary exercise testing (peak V̇O2), assessments of habitual physical activity, body composition (DXA), and asthma questionnaires. Blood was obtained at baseline and post- training program to assess cardiometabolic risk factors. Results: Seventeen of 19 participants completed the study. Adherence to the program was 85%. Based on BMI %ile, 11 of the participants were overweight/obese and 8 were normal weight. Ten participants had persistent asthma. Training was effective as peak V̇O2 improved significantly (8.1%, SD ± 10.4) at the end of the program. There was a significant improvement in lean body mass (1%, SD ± 2.0) and decrease in body fat (1.9%, SD ± 4.6). Asthma quality of life outcomes improved following the intervention in symptoms, emotional function, and overall. Five of 10 participants with persistent asthma were able to decrease their maintenance medications. HDL levels increased significantly from (46.1 ± 8.4 mg/dL to 49.5 ± 10.4 mg/dL, p = 0.04). Discussion: A school-based exercise intervention program designed specifically for children with asthma for a predominantly economically disadvantaged and minority population revealed substantial engagement from the local schools, families and participants. The exercise intervention was effective with improvement in aerobic fitness, body composition, asthma, and lipid outcomes, setting the stage for a larger multicenter trial designed to study exercise as an adjunct medicine in children with asthma.